2017
DOI: 10.1111/ajt.13935
|View full text |Cite
|
Sign up to set email alerts
|

A Steady-State Head-to-Head Pharmacokinetic Comparison of All FK-506 (Tacrolimus) Formulations (ASTCOFF): An Open-Label, Prospective, Randomized, Two-Arm, Three-Period Crossover Study

Abstract: This two‐sequence, three‐period crossover study is the first pharmacokinetic (PK) study to compare all three innovator formulations of tacrolimus (twice‐daily immediate‐release tacrolimus capsules [IR‐Tac]; once‐daily extended‐release tacrolimus capsules [ER‐Tac]; novel once‐daily tacrolimus tablets [LCPT]). Stable renal transplant patients were dosed with each drug for 7 days, and blood samples were obtained over 24 h. Thirty subjects were included in the PK analysis set. A conversion factor of 1:1:0.80 for I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
155
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(184 citation statements)
references
References 32 publications
(37 reference statements)
18
155
0
2
Order By: Relevance
“…Study data from maintenance patients are in accordance with our data 9. The direct comparison of LCPT with IR-Tac in the LCP-Tacro 3002 trial has been biased by the FDA-guided decision to start IR-Tac with a total daily dose of only 0.1 mg/kg (LCPT: 0.17 mg/kg).This led to frequent dose escalations in IR-Tac-patients, whereas patients on LCPT rarely required higher doses.ER-Tac has been started with 0.2 mg/kg, and trough level measurements regularly led to dose escalations (and at least 1 extra dose with IR-Tac in a subset of 12/36 patients).…”
supporting
confidence: 77%
“…Study data from maintenance patients are in accordance with our data 9. The direct comparison of LCPT with IR-Tac in the LCP-Tacro 3002 trial has been biased by the FDA-guided decision to start IR-Tac with a total daily dose of only 0.1 mg/kg (LCPT: 0.17 mg/kg).This led to frequent dose escalations in IR-Tac-patients, whereas patients on LCPT rarely required higher doses.ER-Tac has been started with 0.2 mg/kg, and trough level measurements regularly led to dose escalations (and at least 1 extra dose with IR-Tac in a subset of 12/36 patients).…”
supporting
confidence: 77%
“…Recently, Tremblay and colleagues compared all 3 formulations of tacrolimus (IR-Tac, PR-Tac, and ER-Tac) in 30 stable renal transplant recipients. 20 Patients were dosed with each drug for 7 days, and blood samples were obtained over 24 hours. A conversion factor of 1:1:0.80 for IR-Tac:PR-Tac:ER-Tac was used; no dose adjustments were permitted during the study.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that anti-tumor necrosis factor (anti-TNF) biologics were more likely to achieve mucosal healing than placebo in Crohn's disease (CD) and both anti-TNFs and vedolizumab had higher rates of mucosal healing compared to pla- remains to be determined and validated in prospective studies. 6,7 Last, the optimal time-point to measure mucosal healing for biologics is also unclear, as the time to achieve mucosal healing likely may vary depending on a medication's mode of delivery or mechanism of action.…”
Section: -4mentioning
confidence: 99%
“…6,7 As previously shown, MRS is better than histology in assessing quantitative changes in liver fat in a trial. 8 Despite the short study period, inclusion of MR elastography could have provided valuable additional information as fibrosis stage has been demonstrated to be the most important predictor of morbidity and mortality in NAFLD.…”
mentioning
confidence: 91%